Republic of Turkey : Institutional Review of Energy Efficiency - World Bank (Washington, DC, 2015)
Energy efficiency (EE) is critical to help Turkey continue its trajectory of economic growth in a sustainable manner. The Government of Turkey recognizes this and has placed EE as a key component of its energy strategy and National Climate Change Strategy and Action Plan. Over the past 5-10 years, it has made considerable advances in establishing a strong policy and legal framework, creating a robust institutional set-up and developing programs to support EE implementation. Institutionally, the General Directorate of Electric Power Resources Survey and Development Administration (EIE) had been mandated with EE policy making, implementation and promotion since 1981, and an Energy Efficiency Coordination Board (EECB) was established under the 2007 EE Law to coordinate various EE policies, programs and other efforts. In November 2011, EIE was converted into the General Directorate for Renewable Energy (GDRE) and absorbed within the Ministry of Energy and Natural Resources (MENR). The World Bank conducted an EE institutional review in consultation with the Turkish Government with the objective to enhance their ability to more effectively manage EE policies and programs and thus contribute to helping meet its stated national EE targets. The review consisted of a detailed assessment of the current institutional set-up, including roles and responsibilities for EE in Turkey, along with a comparison with international experience and best practices. A final set of institutional options and recommendations are provided at the end of the report.